THE LINGUISTIC AND SYMBOLIC DIMENSIONS OF JAPANESE FOLKLORE: REFLECTIONS OF A COLLECTIVE (Ustozlar uchun, 2025)
AbstractJapanese folklore, as preserved in Folklore, Folktales, and Fairy Tales from Japan: A Digital Library compiled by D. L. Ashliman, offers profound insight into the cultural consciousness of Japan. Through the linguistic patterns and symbolic imagery embedded within tales such as Momotarō, The Grateful Crane, and The Tongue-Cut Sparrow, one can discern a worldview rooted in harmony with nature, reciprocity, humility, and moral restraint. This paper analyzes how language and symbolism in these folktales encapsulate Japanese values, collective ethics, and philosophical concepts such as wa (harmony) and giri (social obligation).